Multiple familial trichoepithelioma: confirmation via dermoscopy - Cristián Patricio Navarrete-Dechent; Shirin Bajaj; Ashfaq A. Marghoob; Sergio González; Daniel Muñoz (Mattioli1885, 2016)
Trichoepitheliomas are uncommon benign adnexal neoplasms that originate from the hair follicles. Multiple familial trichoepithelioma constitute an autosomal dominant disease characterized by the appearance of multiple flesh-colored, symmetrical papules, tumors and/or nodules in the central face and occasionally on the scalp. Although clinical diagnosis is usually straightforward in light of the family history and naked-eye examination, dermoscopy may aid in its confirmation. Dermoscopy of each papule revealed in-focus arborizing vessels, multiple milia-like cysts and rosettes amidst a whitish background. In a patient with multiple facial papules revealing a dermoscopic appearance described above, the diagnosis of sporadic or familial multiple trichoepithelioma should be considered.